Etiology of Microcephaly and Central Nervous System Defects during the Zika Epidemic in Colombia - Galang, Romeo R.; Avila, Greace Alejandra; Valencia, Diana; Daza, Marcela; Tong, Van T.; Bermúdez, Antonio José; Gilboa, Suzanne M.; Rico, Angélica; Cates, Jordan; Pacheco, Oscar; Winfield, Christina M.; Prieto, Franklyn; et al. (The Journal of pediatrics, 2020)
To estimate the prevalence of microcephaly and central nervous system (CNS) defects during the Zika virus (ZIKV) epidemic in Colombia and proportion attributable to congenital ZIKV infection. Clinical and laboratory data for cases of microcephaly and/or CNS defects reported to national surveillance between 2015 and 2017 were reviewed and classified by a panel of clinical subject matter experts. Maternal and fetal/infant biologic specimens were tested for congenital infection and chromosomal abnormalities. Infants/fetuses with microcephaly and/or CNS defects (cases) were classified into broad etiologic categories (teratogenic, genetic, multifactorial, and unknown). Cases classified as potentially attributable to congenital ZIKV infection were stratified by strength of evidence for ZIKV etiology (strong, moderate, or limited) using a novel strategy considering birth defects unique or specific to ZIKV or other infections and laboratory evidence. Among 858 reported cases with sufficient information supporting a diagnosis of microcephaly or CNS defects, 503 were classified as potentially attributable to congenital ZIKV infection. Of these, the strength of evidence was considered strong in 124 (24.7%) cases; moderate in 232 (46.1%) cases; and limited in 147 (29.2%). Of the remaining, 355 (41.4%) were attributed to etiologies other than ZIKV infection (syphilis, toxoplasmosis, rubella, cytomegalovirus, herpes 1 and herpes 2 viruses only, n = 32 [3.7%]; genetic, n = 16 [1.9%]; multifactorial, n = 42 [4.9%]; unknown, n = 265 [30.9%]). Fifty-eight percent of cases of microcephaly and/or CNS defects were potentially attributable to congenital ZIKV infection; however, the strength of evidence varied considerably. This surveillance protocol might serve as a model approach for investigation and etiologic classification of complex congenital conditions.